Analisis Sistem Informasi Akuntansi Persediaan Terhadap Pengendalian Intern Persediaan Pada PT. Telekomunikasi Selular (TELKOMSEL) Cabang Bogor - Pramiudi, Udi; Prihatin, Rini Yuli; Ulfah, Maria (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
The purpose of this study was to determine the inventory accounting information systems, to determine the internal control inventory and to determine the application of the accounting infomation system of intemal control of inventory at PT. Telkomsel Bogor Branch. The study was a descriptive, in which primary and secondary data were collected by means of observation and documentation techniques. The results show that the discussion of the accounting information system of internal control of inventory of PT. Telkomsel has been running effectively with the division of tasks according to each of their function, limited access to the paradise and the use of system entry and exit of goods shall be in accordance with the data already in the input it was explained that the application ofthe accounting information system inventory control has been going well. Keywords: Inventory Accounting Information Systems, Internal Control Inventory